Tradisi Maserah Sampi Pada Upacara Perkawinan Di Desa Perasan Desa Ban Kecamatan Kubu Kabupaten Karangasem - IG. Agung Jaya Suryawan (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2021)
In Hinduism, the teachings of "Panca Yadnya" are also known, namely five kinds of Yadnya consisting of: Dewa Yadnya, which is an offering to God Almighty and all its manifestations, Pitra Yadnya, an offering to the ancestors, Yadnya Man, an offering made to the ancestors. addressed to fellow human beings, Rsi Yadnya is an offering addressed to Maha Sri who is credited with providing and developing religious teachings, and Butha Yadnya is an offering addressed to the bhuta kala. One form of application of the Human Yadnya teachings carried out by the Hindu community in Bali is a marriage ceremony. In the order of life, Hindu society, especially in Bali, has several forms of marriage according to the instructions from Manawa Darmasastra verse 25-34 it is stated that there are eight kinds of marriage, namely Brahma Wiwaha, Daiwa Wiwaha, Arsa Wiwaha, Prajapati Wiwaha, Asura Wiwaha, Gandarwa Wiwaha, Giant Wiwaha, and Paisaca wiwaha One of the conditions for a valid marriage according to the teachings of Hinduism is known as Tri Upasaksi, namely the Witness God, Witness Human, and Bhuta Witness is a niskala testimony. Niskala testimony is a testimony carried out in the form of a religious ceremony. Meanwhile, the Human Witness is the testimony carried out by the Prajuru, namely the Village Head and Service Officer as well as the community.